DIGITAL SOCIAL PROOF AND CONSUMER PURCHASE DECISION PROCESS IN THE DIGITAL ERA - Didit Darmawan; M. Akmal Maulidi Zamzami (Universitas Negeri Makassar, 2026)
Abstract: This study aims to analyze the mechanisms through which digital social proof influences consumer decision-making processes and to identify factors that moderate the strength of this influence. The research employs a qualitative literature study with a content analysis approach, drawing upon various relevant scholarly sources. The findings indicate that digital social proof operates through quantitative mechanisms, such as review volume and popularity metrics, as well as qualitative mechanisms, including information detail and source identity. Consumers actively evaluate the credibility, relevance, and consistency of social proof in relation to their specific needs. The influence of social proof is not uniform across all consumers but is moderated by factors such as product involvement level, consumer expertise, self-confidence, cultural background, age, purchase objectives, and platform credibility. Authentic and consistent social proof demonstrates greater persuasive power than merely quantitative indicators. The practical implications of this study encourage marketers to develop layered and segmented social proof strategies while prioritizing authenticity over quantity. Regulators and digital platforms also need to play an active role in maintaining the authenticity of social evidence to protect consumers from manipulative practices.Keywords: Social Proof, Consumer Decision-Making, Digital Marketing, Online Reviews, Consumer Behavior, Moderator Factors.